High-Throughput Multiparallel Enteropathogen Detection via Nano-Liter qPCR - Grembi, Jessica A.; Mayer-Blackwell, Koshlan; Luby, Stephen P.; Spormann, Alfred M. (Frontiers in Cellular and Infection Microbiology, 2020)
Quantitative molecular diagnostic methods can effectively detect pathogen-specific nucleic acid sequences, but costs associated with multi-pathogen panels hinder their widespread use in research trials. Nano-liter qPCR (nL-qPCR) is a miniaturized tool for quantification of multiple targets in large numbers of samples based on assay parallelization on a single chip, with potentially significant cost-savings due to rapid throughput and reduced reagent volumes. We evaluated a suite of novel and published assays to detect 17 enteric pathogens using a commercially available nL-qPCR technology. Amplification efficiencies ranged from 88 to 98% (mean 91%) and were reproducible across four operators at two separate facilities. When applied to fecal material, assays were sensitive and selective (99.8% of DNA amplified were genes from the target organism). Due to nanofluidic volumes, detection limits were 1–2 orders of magnitude less sensitive for nL-qPCR than an enteric TaqMan Array Card (TAC). However, higher detection limits do not hinder detection of diarrhea-causing pathogen concentrations. Compared to TAC, nL-qPCR displayed 99% (95% CI 0.98, 0.99) negative percent agreement and 62% (95% CI 0.59, 0.65) overall positive percent agreement for presence of pathogens across diarrheal and non-diarrheal fecal samples. Positive percent agreement was 89% among samples with concentrations above the nL-qPCR detection limits. nL-qPCR assays showed an underestimation bias of 0.34 log10 copies/gram of stool [IQR −0.40, −0.28] compared with TAC. With 12 times higher throughput for a sixth of the per-sample cost of the enteric TAC, the nL-qPCR chip is a viable alternative for enteropathogen quantification for studies where other technologies are cost-prohibitive.